Nanostructured silicon formations as a result of ionized N(2) gas reactions on silicon with native oxide layers - Jung, MC; Lee, TG; Park, YJ; Jun, SH; Lee, J; Han, M; Jeong, JS; Lee, JY (AMER INST PHYSICS, 2003)
Nanostructured silicon was formed by means of the ionized N(2) gas reaction on SiO(2)/Si, and the electronic structure, surface morphology, and optical properties were investigated. The physicochemically modified thin layers were resolved to SiN(y) and SiO(x)N(y) through the observation of Si 2p, O 1s, and N 1s core-level spectra in x-ray photoelectron spectroscopy. The formations of SiOxNy and SiO(2) nanostructures (3-4 nm in size), performed by the etching process followed by adsorption of ionized nitrogen, were confirmed by atomic force microscopy. The nanocrystalline Si (6 nm in size) distributed within the modified layer (approximately 10 nm thick) was observed after the in situ rapid thermal annealing processes, using high-resolution transmission electron microscopy. Photoluminescence with a wavelength peaking at around 400 nm was emitted from the nanocrystalline Si formed from the SiO(x)N(y)/SiO(2)/Si structures. This work suggests that the nanocrystalline-Si formation and the nanostructured surface modification method, using the controlled ionized gas, were simple and efficient methods requiring low energy and low temperatures. (C) 2003 American Institute of Physics.
Keywords: AMORPHOUS-SILICON; SI NANOCRYSTALS; CRYSTALLIZATION; EMISSION; HYDROGEN